Production estimation and delay analyses of a locally fabricated band saw (2020)
The objective of the study was to estimate the productivity of a locally fabricated band saw using delay analyses in order to achieve improved production and judicious utilisation of available resources. A time and motion study was applied to collect the data for the processing system and the data recorded and processed. The working cycle of the machine was also recorded and all variables that affect productivity. The result shows productivity was significantly affected by the log supplied characteristics, sawing patterns, maintenance of equipment and level of training. This reveals the need to improve equipment availability and maintenance during sawing.